Honey as an Alternative Dressing in Post-Palatoplasty—Two Case Reports - Clara David; Irfan Rasul; Yossy Y. Ariestiana; Abul Fauzi (Case Reports in Medicine)
Palatoplasty is a surgical procedure used to repair a cleft palate. Postsurgery there are times when the healing process is disrupted. Honey has been utilised since ancient times as an antibacterial, anti-inflammatory, and regenerative treatment for wounds, and it has been shown to expedite the wound healing process by promoting the formation of new tissue.